AN INTRODUCTION TO VARIABLE STARS IN ASTRONOMY - KOKNE, P.M.; ARDAD, A.N. (Innovare Journal of Sciences, 2020)
Objective: The Variable Star (brightness changes) of these stars can range from a thousandth of a magnitude to as much as twenty magnitudes over periods of a fraction of a second to years, depending on the type of variable star. Over 150,000 variable stars are known and catalogued, and many thousands more are suspected to be variable. There are a number of reasons why variable stars change their brightness. Some variable stars are actually extremely close pairs of stars, exchanging mass as one star strips the atmosphere from the other. Variable stars are classified as either intrinsic, wherein variability is caused by physical changes such as pulsation or eruption in the star or stellar system, or extrinsic, wherein variability is caused by the eclipse of one star by another, the transit of an extrasolar planet, or by the effects of stellar rotation. Methods: We can choose a ‘model’ of a given star by requiring that it reproduce the observed variability as well as the other observed characteristics of the star. From the model, we can then learn about the internal composition, structure, and physical processes in the star. Astronomers have studied all types of stars, on all time scales from milliseconds to centuries, in all regions of the spectrum. Conclusion: Variable stars provide important information about astrophysical processes, about the nature and evolution of stars, and even about the size, age, and evolution of the universe. Variable star observation and analysis are inherently simple, but the actual techniques of analysis and interpretation involve a wide range of scientific and mathematical skill.